Evaluating Terminator Strength Based on Differentiating Effects on Transcription and Translation. (9th April 2020) - He, Zhiyun; Duan, Yanting; Zhai, Weiji; Zhang, Xiaomei; Shi, Jinsong; Zhang, Xiaojuan; Xu, Zhenghong
Abstract: Transcription terminators play a role in terminating the progress of gene transcription, and are thus essential elements in the gene circuit. Terminators have two main functions: terminating gene transcription and improving the stability of gene transcripts during translation. We therefore considered the detailed characteristics of terminators in relation to their different roles in gene transcription and translation, including transcription shut‐down degree ( α ) and upstream mRNA protection capacity ( β ), and apparent termination efficiency ( η ) reflecting the overall regulatory effect of the terminator. Based on a dual‐reporter gene system, we constructed three terminator‐probe plasmids to investigate each characteristic in Escherichia coli . According to multiple regression analysis, the transcription shut‐down degree and the upstream mRNA protection capacity contributed almost equally to the apparent termination efficiency. Sequence analysis of 12 terminators demonstrated that the terminator sequence was dominated by GC bases, and that a high ratio of GC bases in the stem structure of terminators might be associated with a high degree of transcription shut‐down. This comprehensive characterization of terminators furthers our understanding of the role of terminators in gene expression and provides a guide for synthetic terminator design. Abstract : Transcription terminators not only regulate gene transcription but also affect mRNA stability. We characterized terminators in terms of degree of transcription shut‐down and capacity for upstream mRNA protection by using different terminator probe plasmids to determine the contribution of both characteristics to the overall termination effect, and to investigate the sequence characteristics associated with transcription shut‐down degree.